A novel phosphorus−silicon containing epoxy resin with enhanced thermal stability, flame retardancy and mechanical properties. (June 2019) - Li, Jialiang; Wang, Hongyu; Li, Shichao
Abstract: A novel phosphorus−silicon containing epoxy resin (EF−P/Si) was prepared by introducing a phosphoric triamide (PTA) and epoxy−functionalized polysiloxane (EFP) into the Bisphenol F epoxy resin/4, 4′−diaminodiphenyl methane (DDM) system to improve its flame retardancy and mechanical properties. PTA was synthesized by Triethyl phosphate and DDM and EFP was prepared by dimethyldimethoxysilane, dimethoxydiphenylsilane and 3−glycidoxy−propyltrimethoxysilane. TGA results demonstrated that EF−P/Si yielded a char residue of up to 16.6% at 700 °C. The measurements of flame retardancy showed that LOI value of EF−P/Si was 30.2, 50% higher than that of the pure epoxy resin and its UL−94 grade reached to V−1. A decomposition test under air was carried out to further investigate thermal stability of EF−P/Si. EF−P/Si exhibited a compact char structure which acted as a protective layer to inhibit the decomposition of the underlying matrix. EDX and FTIR verified that PSi synergistic effect played a role in improving thermal stability of the char residue. The results of the mechanical property test showed that the incorporation of PTA and EFP significantly enhanced failure strain and KIC of the epoxy resin without sacrificing its tensile strength, which was attributed to the increased free volume in the cured network and the excellent flexibility of the −SiOSi− skeleton in EFP. Highlights: A novel P−Si containing epoxy resin was prepared. The P−Si containing epoxy resin possessed higher thermal stability above 400 °C and flame retardancy. The P−Si containing epoxy resin exhibited obviously enhanced failure strain and KIC .